Rihanna versus Bollywood: Twitter Influencers and the Indian Farmers’ Protest - Mishra, Dibyendu; Akbar, Syeda Zainab; Arya, Arshia; Dash, Saloni; Grover, Rynaa; Pal, Joyojeet (2021)
A tweet from popular entertainer and businesswoman, Rihanna, bringing attention to farmers’ protests around Delhi set off heightened activity on Indian social media. An immediate consequence was the weighing in by Indian politicians, entertainers, media and other influencers on the issue. In this paper, we use data from Twitter and an archive of debunked misinformation stories to understand some of the patterns around influencer engagement with a political issue. We found that more followed influencers were less likely to come out in support of the tweet. We also find that the later engagement of major influencers on the side of the government’s position shows suggestion’s of collusion. Irrespective of their position on the issue, influencers who engaged saw a significant rise in their following after their tweets. While a number of tweets thanked Rihanna for raising awareness on the issue, she was systematically trolled on the grounds of her gender, race, nationality and religion. Finally, we observed how misinformation existing prior to the tweet set up the grounds for alternative narratives that emerged.